Impact of substrate temperature on the properties of yttrium oxide thin films prepared by nebulizer spray pyrolysis technique. (2022) - Thangabalu, S.; Senthil kumar, N.; Usha devi, T.; Selvi, S.; Chang, J.H.; Mohanraj, K.
Abstract: In this study, the yttrium oxide (Y2 O3 ) thin films were prepared at different substrate temperatures (Tsub ) 300 °C, 350 °C, 400 °C, 450 °C, and 500 °C by nebulizer spray pyrolysis technique. Structural studies confirm the formation of Y2 O3 in the cubic phase. The trap rock structure was obtained from the SEM micrograph. It was observed that the yttrium oxide thin films show better particle growth at higher substrate temperatures. XRD results reveal that the crystalline nature of the Y2 O3 thin films increased with the increasing of substrate temperatures, and the SEM morphology grain size will decrease in higher temperatures, which is good agreement with the XRD results. The optical bandgap varied from 2.58 to 3.6 eV among an increased substrate temperature from 350 °C to 500 °C. The recorded photoluminance spectra of Y2 O3 thin films exhibit a sharp and broad emission at 310 nm and 466 nm.